Con Marco Aguilar - Chase, Alfonso (2024)
This brief text, written by Alfonso Chase, a well-known poet, novelist, short story writer, essayist, literary researcher and cultural promoter, corresponds to the presentation of a selection of poems by Marco Aguilar, published in 1964 in the supplement Página Literaria, in La República Newspaper.